Does instant coffee prevent acute liver injury induced by carbon tetrachloride(CCl4)? - Ozercan, Ibrahim Hanifi; Dagli, Adile Ferda; Ustundag, Bilal; Ozercan, Mehmet Resat; Bahcecioglu, Ibrahim Halil; Celik, Hakim; Ataseven, Huseyin (Wiley-Blackwell, 2006)
Objective: To investigate the protective effect of instant coffee (IC) on acute liver injury induced by CCl4. Methods: The study included 32 rats which were allocated to four groups: control (n: 8), CCl4 (n: 8), CCl4 + IC (n: 8) and IC (n: 8). Malondialdehyde, which is a lipid peroxidation product, and levels of antioxidant capacity were measured and histopathological data were compared. Results: It was seen in the study that lipid peroxidation products that increased in the plasma and liver tissue of the CCl4 group decreased by IC administration. There was an increase in the measured antioxidant parameters, which were total antioxidant capacity (TAOC), sulphydryl (SH) and ceruloplasmin levels. Histopathologically, it was found that inflammation and necrosis which increased in the group administered CCl4 decreased significantly with IC administration, but there steatosis did not change. Conclusions: It was seen that IC had a protective role in acute liver injury induced by CCl4, but did not affect steatosis, (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: instant coffee; acute liver injury; lipid peroxidation; antioxidant